Reply to: Broadening concepts of core pathobiology in various aspects of COPD development. Issue 6 (8th December 2022) - Xu, Feng; Vasilescu, Dragos; Tan, Wan; Hogg, Jim; Hackett, Tillie-Louise
We thank E.H. Walters and co-workers for highlighting the innovation of our study [1] using micro-computed tomography (micro-CT) imaging to match tissue pathology with its gene transcriptome, in order to understand the pathobiology of small airway disease in end-stage COPD. We agree with the authors that post-transplant, explanted COPD lungs do represent the end stages of the disease; however, such lung samples provide the only opportunity to assess the entire lung structure and the heterogeneity of small airway disease and emphysema across lung height without the presence of cancer. As the authors note, we have previously shown that destruction of the last generation of small conducting airways, the terminal bronchioles, precedes emphysematous tissue destruction in end-stage COPD [2]. More recently, this work has been validated using formalin-fixed-paraffin embedded (FFPE) samples from patients with mild and moderate COPD, which demonstrated over 41% of their terminal bronchioles are destroyed prior to the detection of emphysema on clinical CT or microscopically on micro-CT [3]. These data highlight that loss of terminal bronchioles occurs early in the disease process and understanding the pathobiology of terminal bronchiole reduction has the potential to develop new therapeutics for COPD. Understanding the pathology of COPD by assessing the "hot spots" or earliest regions of small airway disease https://bit.ly/3SSql1L